Influence of the Gravitational Darkening Effect on the Spectrum of a Hot, Rapidly Rotating Neutron Star. II. Iron Lines - Agnieszka Majczyna; Jerzy Madej; Agata Różańska; Mirosław Należyty (The Astrophysical Journal, 2024)
Rapidly rotating neutron stars are similar to highly flattened ellipsoids. Observed spectra of flattened stars must exhibit effects of nonspherical shape and gravitational darkening. We examined in detail the influence of both effects on the observed central energies and profiles of lines of highly ionized iron, Fe xxv and Fe xxvi . We note that the gravitational darkening effect does not change the central energy of lines. Most importantly, spectra of neutron stars that rotate with different frequencies and are seen at various inclination angles differ significantly. The appearance and the depth of lines strongly depend on the parameters, like the inclination angle of the star or the frequency of the star rotation. In this paper we clearly show that the gravitational darkening effect should be included in realistic models of the atmospheres of the neutron stars.